Influence of shot peening on the fatigue strength of Custom 465 stainless steel for aeronautic application - Bonora, Rafael Gustavo [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Clark, G.; Wang, C. H. (Trans Tech Publications Ltd, 2014)
This project was originated from the national aircraft industry requirements to reduce the use of coated materials with electroplated chromium or cadmium that produce waste, which is harmful to health or the environment. The selected material is a Custom 465 stainless steel used in the aeronautical field due to its high mechanical strength. Considering the load sustained by the wheel axis of the landing gear, the Custom 465 is tested in axial fatigue. The objective is to compare the behavior of the Custom 465 with plated AISI 4340 steel coated with cadmium. X-ray diffraction method was used to determine the residual stress field induced by shot peening.
Keywords: Fatigue; Custom 465; AISI 4340 steel